Organic potassium-based ion battery based on salting-out effect and preparation method thereof
By controlling the molar ratio and salting effect of organic potassium salt to ether electrolytes, the dissolution of organic positive electrode materials is inhibited, and the SEI film formation of graphite negative electrodes is promoted, which solves the problems of easy soluble and poor cycle stability of organic electrode materials, which significantly improves the Cycle life and electrochemical properties of organic potassium-based batteries.
Patent Information
- Application Number
- CN202411215252.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
Existing organic electrode materials are easily soluble in electrolytes, resulting in significant capacity degradation and poor cycle life. The cured electrolytes have electrochemical kinetic hysteresis, which limits their rate performance and cycle stability.
By controlling the molar ratio of organic potassium salts and ether electrolytes, salt ions compete with organic molecules to participate in the solvation effect, reducing the interaction between solvents and organic molecules, combining with salting effect, inhibiting the dissolution of organic positive electrode materials, and promoting the Anion-derived SEI film is formed on the surface of the graphite negative electrode, which improves cycling stability.
Without affecting the activity of the positive electrode material, the solubility of the positive electrode material is greatly reduced, the cycle stability of the organic positive electrode and the structural stability of the graphite negative electrode are improved, and the cycle life of the organic potassium-based battery is significantly improved.
Smart Images

Figure CN119208707A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a methyl ion battery, in particular to an organic potassium-based ion battery based on a salting-out effect and a preparation method thereof, belonging to the technical field of methyl ion batteries. Background Art
[0002] Rechargeable potassium-based batteries have the advantages of low cost, high operating voltage, and compatibility with graphite anodes, and have broad development prospects. Compared with layered oxides, Prussian blue analogs, and polyanionic compounds, organic electrode materials show great potential due to their low cost, sustainability, and environmental friendliness. However, most organic electrode materials are easily soluble in electrolytes, resulting in significant capacity degradation and poor cycle life. The easy solubility problem of organic electrode materials can be alleviated by several techniques, such as separator engineering, molecular polymerization, and electrolyte solidification. Among them, separator engineering and molecular polymerization require complex procedures, which will greatly reduce the battery capacity when more and more inactive materials such as additives that do not contribute to the capacity of the battery are used. Therefore, the problem of easy solubility of organic electrode materials still exists, and their cycle stability needs to be further improved. Due to low ionic conductivity and high interfacial resistance, solidified electrolytes usually have the problem of electrochemical kinetic hysteresis, which limits their rate performance and cycle stability. Therefore, it is urgent to explore new methods to effectively inhibit the dissolution of organic electrode materials without sacrificing other properties.
[0003] Proteins are typical organic macromolecules whose solubility changes with solvent concentration. Under low salt concentration conditions, the addition of salt will destroy the electrostatic interaction between proteins and lead to increased solubility, which is called salt dissolution, in which the increased ionic strength of the solution leads to increased solubility of the solute. Under high salt concentration conditions, salt ions compete with proteins and participate in solvation, resulting in decreased protein solubility and precipitation, which is called salting out. The salting out effect has been successfully applied to protein purification, water treatment and chemical synthesis. Summary of the invention
[0004] In view of the problems existing in the prior art, the first object of the present invention is to provide an organic potassium-based ion battery based on the salting-out effect. The potassium-based ion battery controls the molar ratio of the organic potassium salt to the ether electrolyte, maintains the electrolyte in a specific concentration range, and utilizes the effect of salt ions competing with organic molecules to participate in solvation, prompting the solvent molecules to tend to interact with the salt ions, thereby reducing the amount of interaction between the solvent and the organic molecules, and achieving the technical purpose of significantly reducing the solubility of the positive electrode material without affecting the activity of the positive electrode material.
[0005] The second object of the present invention is to provide a method for preparing an organic potassium-based ion battery based on the salting-out effect. The method has the advantages of low cost, flexible design and simple process, and utilizes the principle of the salting-out effect to inhibit the dissolution of the organic positive electrode material, thereby improving the cycle stability of the organic positive electrode, and at the same time promoting the formation of anion-derived SEI film on the surface of the graphite negative electrode to improve the structural stability of the graphite negative electrode, thereby greatly improving the cycle life of the organic potassium-based battery.
[0006] In order to achieve the above technical purpose, the present invention provides an organic potassium-based ion battery based on salting-out effect, comprising an organic positive electrode, a potassium salt electrolyte, a negative electrode and a separator;
[0007] The active material of the organic positive electrode is a high molecular polymer; the potassium salt electrolyte comprises an organic potassium salt and an ether electrolyte, and the molar ratio of the two is 1:1-2.
[0008] As a preferred solution, the raw material of the high molecular polymer is at least one of p-phenanthracene dianhydride, perylenetetracarboxylic dianhydride, tea-N,N-bis(iminoamine), anthraquinone-1,5-disulfonic acid sodium salt and polyaniline.
[0009] As a preferred solution, the organic potassium salt is bis(fluorosulfonyl)imide potassium salt, and the ether electrolyte is ethylene glycol dimethyl ether.
[0010] As a preferred solution, the molar ratio of the potassium bis(fluorosulfonyl)imide salt to ethylene glycol dimethyl ether is 1:1 to 1.5. More preferably, the molar ratio of the potassium bis(fluorosulfonyl)imide salt to ethylene glycol dimethyl ether is 1:1.2.
[0011] As a preferred solution, the active material of the organic positive electrode is polyaniline and / or perylenetetracarboxylic dianhydride, wherein the structure of polyaniline is a completely reduced all-benzene structure.
[0012] As a preferred solution, the perylenetetracarboxylic dianhydride needs to be calcined at 400-500° C. for 3-5 hours in an argon environment before use.
[0013] The present invention also provides a method for preparing an organic potassium-based ion battery based on the salting-out effect, comprising:
[0014] 1) mixing a conductive agent, a binder, an active material of an organic positive electrode and a dispersing solvent to obtain a slurry, coating the slurry on an aluminum foil current collector, and drying the slurry to obtain a positive electrode of a battery;
[0015] 2) mixing a conductive agent, a binder, graphite and a dispersing solvent to obtain a slurry, coating the slurry on a copper foil current collector, and drying the slurry to obtain a negative electrode of the battery;
[0016] 3) Assemble the battery positive electrode, battery negative electrode, electrolyte and glass fiber separator.
[0017] As a preferred solution, the preparation process of the active material of the organic positive electrode is: adding aniline to a hydrochloric acid solution to obtain a mixed solution A; mixing ammonium persulfate and the hydrochloric acid solution to obtain a mixed solution B; mixing the mixed solutions A and B to perform a polymerization reaction, and after the reaction is completed, washing and drying to obtain the active material.
[0018] As a preferred solution, the concentration of the hydrochloric acid solution is 1-4 mol / L.
[0019] As a preferred solution, during the preparation process of the active material of the organic positive electrode, except for cleaning and drying, the ambient temperature is below 0°C.
[0020] As a preferred solution, the cleaning and drying process is: first rinse with deionized water for 3 to 5 times, then centrifuge and wash, and after washing, dry in a vacuum drying oven at 60 to 80° C. for 12 to 16 hours.
[0021] As a preferred solution, the conductive agent is acetylene black, the adhesive is PVDF, and the dispersant is N-methylpyrrolidone.
[0022] As a preferred solution, in the process of preparing the positive electrode of the battery, the mass ratio of the conductive agent, the binder and the active material is 6 to 9:1 to 3:1. More preferably, in the process of preparing the positive electrode of the battery, the mass ratio of the conductive agent, the binder and the active material is 7:2:1.
[0023] As a preferred solution, during the preparation of the battery negative electrode, the mass ratio of the conductive agent, the binder and the graphite is 6 to 9: 1 to 3: 1. More preferably, during the preparation of the battery negative electrode, the mass ratio of the conductive agent, the binder and the graphite is 8: 1: 1.
[0024] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:
[0025] 1) The potassium-based ion battery provided by the present invention controls the molar ratio of the organic potassium salt to the ether electrolyte to maintain the electrolyte within a specific concentration range, and utilizes the effect of salt ions competing with organic molecules for solvation, prompting the solvent molecules to tend to interact with the salt ions, thereby reducing the amount of interaction between the solvent and the organic molecules, thereby achieving the technical purpose of significantly reducing the solubility of the positive electrode material without affecting the activity of the positive electrode material.
[0026] 2) The preparation method provided by the present invention has the advantages of low cost, flexible design and simple process. It utilizes the principle of salting-out effect to inhibit the dissolution of organic positive electrode materials, thereby improving the cycle stability of the organic positive electrode. At the same time, it promotes the formation of anion-derived SEI film on the surface of the graphite negative electrode to improve the structural stability of the graphite negative electrode, thereby greatly improving the cycle life of the organic potassium-based battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the salting-out effect used in the embodiment of the present invention;
[0028] Figure 2 Optical photographs and UV-visible absorption spectra of the electrolyte, polyaniline and PTCDA in the embodiments of the present invention;
[0029] in, Figure 2 A is a schematic diagram of the solubility of polyaniline and PTCDA in electrolytes of different concentrations. Figure 2 B is a schematic diagram of UV-visible light absorption test. Figure 2 C above and below are the supernatants obtained after PANI (upper) and PTCDA (lower) were immersed in electrolytes with different KFSI:DME molar ratios for three hours. Figure 2 D and Figure 2 E is the UV-visible absorption spectrum test of the corresponding supernatants of PANI (2D) and PTCDA (2E);
[0030] Figure 3 Schematic diagram of molecular dynamics simulation of polyaniline in electrolytes of different concentrations according to an embodiment of the present invention;
[0031] in, Figure 3 A is the dispersion of polyaniline in pure DME, Figure 3 B is the dispersion of polyaniline when KFSI:DME is 1:12.5. Figure 3 C is the dispersion of polyaniline when KFSI:DME is 1:1.2;
[0032] Figure 4 Schematic diagram of Raman spectra and radial distribution functions of electrolytes with different concentrations used in the embodiments of the present invention;
[0033] in, Figure 4 A is the Raman spectra of electrolytes with different KFSI:DME molar ratios. Figure 4 B is a schematic diagram of the radial distribution function of the electrolytes KFSI:DME=1:12.5 and KFSI:DME=1:1.2, Figure 4 C is the distribution of SSIP, CIP, and AGG for KFSI:DME=1:12.5 (upper) and KFSI:DME=1:1.2 (lower);
[0034] Figure 5 This is a test diagram of the electrochemical performance of the polyaniline half-cell provided in an embodiment of the present invention based on KFSI:DME=1:1.2 electrolyte;
[0035] in, Figure 5 A is the rate performance test diagram of PANI|K half-cell at 2~4V voltage. Figure 5 B is the cycle performance test diagram of PANI|K half-cell at 2~4V. Figure 5 C is the schematic diagram of the CV curve of the half-cell. Figure 5 D is the voltage of 2~4.4V, PANI|K half-cell at 2Ag -1 Schematic diagram of the charge and discharge voltage curves under current density; Figure 5 E is a schematic diagram of the cycling performance of the PANI|K half-cell at 2 to 4.4 V;
[0036] Figure 6 An in-situ impedance test diagram of a polyaniline half-cell of a polyaniline half-cell provided by an embodiment of the present invention;
[0037] Figure 7 The electrochemical performance test diagram and microscopic morphology schematic diagram of the graphite half-cell provided in the embodiment of the present invention;
[0038] in, Figure 7 A is the charge and discharge curve of K|graphite in KFSI:DME 1:100, 1:10 and 1:2 electrolyte conditions, Figure 7 B is a comparison chart of the cycle performance of graphite half-cells based on three different electrolytes. Figure 7 CE is a SEM diagram of the graphite negative electrode after 20 cycles of graphite half-cells based on three different electrolytes;
[0039] Figure 8 A schematic diagram showing the graphite structure after the graphite half-cell cycle according to an embodiment of the present invention;
[0040] in, Figure 8 A, B and C are XRD diagrams under the conditions of KFSI:DME 1:100, 1:10 and 1:2 electrolyte, respectively; Figure 8 D, E and F are schematic diagrams of the atomic ratio of C and O on the graphite surface after different cycles obtained by energy dispersive spectroscopy mapping under the conditions of KFSI:DME 1:100, 1:10 and 1:2 electrolytes, respectively;
[0041] Fig. 9 This is a performance test diagram of a soft-pack battery based on KFSI electrolyte, polyaniline positive electrode, PTCDA positive electrode and graphite negative electrode provided in an embodiment of the present invention;
[0042] in, Fig. 9 A is a performance test diagram of the polyaniline positive electrode soft pack; Fig. 9 B and C are the soft pack performance test diagrams of PTCDA positive electrode. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. The materials, reagents, etc. used in the present invention, unless otherwise specified, can all be obtained from commercial sources.
[0044] Example 1
[0045] The present invention provides a method for preparing a polyaniline organic positive electrode, comprising the following steps:
[0046] First, a certain amount of aniline and ammonium persulfate are mixed and added into a 1-4 mol / L hydrochloric acid (HCl) solution and placed under sub-zero conditions for 4 hours;
[0047] Secondly, a certain amount of ammonium persulfate is mixed with 1-4 mol / L HCl solution and placed under sub-zero conditions for 4 hours;
[0048] Mix the two liquids again and stir them at 0°C for 2 to 4 hours;
[0049] Finally, the product is rinsed repeatedly with deionized water for 3 to 5 times, and then centrifuged and washed. The washed product is placed in a vacuum drying oven at 60 to 80° C. and dried for 12 to 16 hours to obtain polyaniline.
[0050] like Figure 2 As shown in A, polyaniline was immersed in electrolytes of different concentrations of KFSI:DME. After standing for 3 days, the electrolyte supernatant showed different colors. The darker the color, the more polyaniline dissolved in the electrolyte. Increasing the concentration of the electrolyte, the solubility of polyaniline increased, reflecting the salting effect. Continuing to increase the concentration of the electrolyte, the solubility of polyaniline gradually decreased, reflecting the salting-out effect. Figure 2 C shows that the analysis of the ultraviolet-visible absorption spectrum of the supernatant of the electrolyte also proves that the solubility of polyaniline shows a trend of first increasing and then decreasing with the increase of the electrolyte concentration.
[0051] like Figure 4As shown in Figure A, the solvation structures of various KFSI:DME electrolytes were studied by Raman spectroscopy, where x in KFSI:DME=1:x represents the molar ratio of DME solvent to KFSI. The Raman peak at 700-760 cm-1 is caused by FSI-vibration. Obviously, with the increase of electrolyte concentration, the FSI peak shifted, indicating that the number of free FSI anions decreased, while the contact ion pairs (CIP) and agglomerates (AGG) increased. At the same time, with the increase of electrolyte concentration, the Raman peak at 840-870 cm-1 (DME) also shifted, indicating that the free DME gradually decreased.
[0052] Battery Assembly:
[0053] All electrochemical testing was performed in either 2032-size coin cell or pouch cell configurations.
[0054] All coin cells were fabricated in an argon-filled glove box, and glass fiber (Whatman, GF / D) was used as separator.
[0055] Active polyaniline, conductive agent (acetylene black) and PVDF binder (weight ratio 7:2:1) were mixed in NMP (AR, 99%, Aladdin) solution and stirred overnight. The positive electrode was prepared by spreading the slurry on an aluminum foil current collector and then drying at 80 ° C for 24 hours; the polyaniline electrode was cut into a circle with a diameter of 1.2 cm for coin cells (CR2032). The active material loading was about 1.2 mg cm-2.
[0056] Graphite, conductive agent (acetylene black) and PVDF binder (weight ratio 7:2:1) were mixed in NMP solution and stirred overnight. The negative electrode was prepared by spreading the slurry on a copper foil current collector and then drying at 80 °C for 24 hours; the graphite electrode was cut into a circular shape with a diameter of 1.2 cm for coin cells (CR2032).
[0057] Practical application test of the battery: polystyrene board, KFSI:DME=1:1.2, graphite are used to form a soft pack battery. The test results are shown in Fig. 9 , it can be seen that the battery can be stably charged and discharged, and has a relatively stable long cycle.
[0058] In summary, the present invention provides an organic potassium-based battery that utilizes the salting-out effect of protein to inhibit the dissolution of organic positive electrode materials. In a high-concentration electrolyte, the free DME molecules are significantly reduced in the electrolyte of KFSI@DME because the solvation structure is mainly AGG. Since there is almost no free DME interacting with polyaniline, the solubility of polyaniline is reduced. For the graphite negative electrode, the high-concentration electrolyte promotes the formation of anion-derived SEI to obtain an organic battery with strong reversibility and stable cycle. It is worth noting that the present invention provides a method for inhibiting the dissolution of the organic positive electrode by utilizing the salting-out effect, so that the PTCDA positive electrode soft-pack battery achieves a high capacity of 99.6mAh. Therefore, the organic potassium-based battery based on the salting-out effect provided by the present invention exhibits excellent electrochemical properties, which can point the way for the further development of high-performance organic potassium-based batteries.
[0059] Although the specific implementation method of the present invention is described above, those skilled in the art should understand that the specific embodiments described are only illustrative and not limiting on the scope of the present invention. The equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. An organic potassium-based ion battery based on salting-out effect, characterized in that: It includes an organic positive electrode, a potassium salt electrolyte, a negative electrode and a separator; The active material of the organic positive electrode is a high molecular polymer; the potassium salt electrolyte comprises an organic potassium salt and an ether electrolyte, and the molar ratio of the two is 1:1-2.
2. An organic potassium-based ion battery based on salting-out effect according to claim 1, characterized in that: The raw material of the high molecular polymer is at least one of p-phenanthracene dianhydride, perylenetetracarboxylic dianhydride, tea-N, N-bis(iminoamine), anthraquinone-1,5-disulfonic acid sodium salt and polyaniline.
3. An organic potassium-based ion battery based on salting-out effect according to claim 1, characterized in that: The organic potassium salt is bis(fluorosulfonyl)imide potassium salt, and the ether electrolyte is ethylene glycol dimethyl ether; the molar ratio of the bis(fluorosulfonyl)imide potassium salt to ethylene glycol dimethyl ether is 1:1-1.
5.
4. An organic potassium-based ion battery based on salting-out effect according to claim 1 or 2, characterized in that: The active material of the organic positive electrode is polyaniline and / or perylenetetracarboxylic dianhydride, wherein the structure of polyaniline is a completely reduced all-benzene structure.
5. The method for preparing an organic potassium-based ion battery based on salting-out effect according to any one of claims 1 to 4, characterized in that: include: 1) mixing a conductive agent, a binder, an active material of an organic positive electrode and a dispersing solvent to obtain a slurry, coating the slurry on an aluminum foil current collector, and drying the slurry to obtain a positive electrode of a battery; 2) mixing a conductive agent, a binder, graphite and a dispersing solvent to obtain a slurry, coating the slurry on a copper foil current collector, and drying the slurry to obtain a negative electrode of the battery; 3) Assemble the battery positive electrode, battery negative electrode, electrolyte and glass fiber separator.
6. The method for preparing an organic potassium-based ion battery based on salting-out effect according to claim 5, characterized in that: The preparation process of the active material of the organic positive electrode is as follows: adding aniline to a hydrochloric acid solution to obtain a mixed solution A; mixing ammonium persulfate and the hydrochloric acid solution to obtain a mixed solution B; mixing the mixed solutions A and B to perform a polymerization reaction, and after the reaction is completed, washing and drying to obtain the active material.
7. The method for preparing an organic potassium-based ion battery based on salting-out effect according to claim 6, characterized in that: The concentration of the hydrochloric acid solution is 1-4 mol / L; during the preparation of the active material of the organic positive electrode, the ambient temperature is below 0° C. except for cleaning and drying.
8. The method for preparing an organic potassium-based ion battery based on salting-out effect according to claim 6, characterized in that: The cleaning and drying process is as follows: firstly rinse with deionized water for 3 to 5 times, then perform centrifugal washing, and after washing, dry in a vacuum drying oven at 60 to 80° C. for 12 to 16 hours to obtain the product.
9. The method for preparing an organic potassium-based ion battery based on salting-out effect according to claim 5, characterized in that: The conductive agent is acetylene black, the adhesive is PVDF, and the dispersant is N-methylpyrrolidone.
10. The method for preparing an organic potassium-based ion battery based on salting-out effect according to claim 5, characterized in that: In the process of preparing the positive electrode of the battery, the mass ratio of the conductive agent, the adhesive and the active material is 6-9:1-3:1; in the process of preparing the negative electrode of the battery, the mass ratio of the conductive agent, the adhesive and graphite is 6-9:1-3:1.
